Analysis of Mandatory Health Financing Mechanisms After the Abolition of Mandatory Health in Law No. 17 of 2023 - Kusna, Akit Afit Datul; Kurniawan, Bachtiar Dwi; Nurmandi, Achmad; Fridayani, Helen Dian (Journal Public Policy, 2024)
The process of formulating policy is a complex matter. During the preparation and ratification of the policy, there will be pros and cons. Included the pros and cons of the loss of the mandatory health budget in Law No. 17 concerning health in 2023. The government's reason for eliminating the mandatory health budget is there is still corruption, and the budget allocation used needs to be more effective and efficient. This study aims to analyze the government's mechanism for financing the health sector, which is considered more efficient after the mandatory health budget is removed. This research uses a qualitative method with official news media as the data source. The data collected came from five official mass media news sources totaling 50 news articles. Data analysis with NVivo 12 plus aims to visualize data from news media. The analysis techniques in this research are data reduction, data presentation, and conclusion drawing. The results of this study indicate that the policy of eliminating the mandatory health budget is replaced with a "money follow program" so that the health budget becomes efficient. Budget spending is based on the health program development plan contained in the Health Sector Master Plan. The limitations of this study are that it only uses secondary data derived from mass media online news totaling 50 and only uses NVivo 12 plus tools, so it is hoped future research can use primary data to comprehensively discuss the quality of health in Indonesia after the mandatory health budget is removed.